Comparative Transcriptomic Analysis Reveals Adaptive Traits in Antarctic Scallop Adamussium colbecki - Samuele Greco; Giacomo Voltarel; Anastasia Serena Gaetano; Chiara Manfrin; Alberto Pallavicini; Piero Giulio Giulianini; Marco Gerdol (Fishes, 2023)
Antarctica is the most extreme continent of Earth, with strong winds, freezing temperatures on land, and ocean temperatures constantly below 0 °C. Nonetheless, the Antarctic Ocean is home to an astounding diversity of living organisms that adapted to the multiple challenges posed by this environment via a diverse set of evolutionary traits. Although the recent advancements in sequencing technologies clarified the molecular bases of such adaptations in Antarctic fishes, little information is available for Antarctic invertebrates. In this preliminary study, we address this knowledge gap with a comparative transcriptomic approach to obtain insights into some of the adaptations that allow the Antarctic scallop Adamussium colbecki to survive and thrive in the freezing waters of the Antarctic Ocean. Despite some limitations, our analyses highlighted significant over-expression of genes involved in regulation of mRNA transcription, maturation, and degradation, which might compensate for a reduced efficiency of these processes at low temperatures. Other alterations detected in the Antarctic scallop transcriptome include enhanced expression of genes that regulate degradation of misfolded protein products and allow maintenance of cytoskeletal structure and function at subzero temperatures. Altogether, these observations support the presence of multiple previously unreported molecular adaptive traits in A. colbecki, which have important implications for our understanding of adaptation of this important component of the Antarctic trophic chain to such an extreme, but stable environment.